The effects of lincomycin-spectinomycin and sulfamethoxazole-trimethoprim on hyaluronidase activities and sperm characteristics of rams - Tanyildizi, S; Bozkurt, T (Japan Soc Vet Sci, 2003)
The effects of lincomycin-spectinomycin and sullamethoxazole-trimethoprim combinations on the hyaluronidase enzyme of serum and semen and on sperm characteristics in rams were determined. Thirthy-two Akkaraman rams were used. The rams were randomly divided into four groups. Group A and group B were determined as control groups of group C (lincomycin-spectinomycin) and D (sulfamethoxazole-trimethopim), respectively. Combinations of lincomycin-spectmomycin and sulfamethoxazole-trimethoprim were administered at doses of 15 mg.kg(-1) intramuscularly and 12 mg.kg(-1) body weights orally, respectively. Blood and semen samples were collected at 4, 12, 24, 48, 72, 192 and 384 hr. Semen hyaluronidase activities of rams in group C increased significantly (p<0.001, <0.05) compared with the control group at 24 and 48 hr, respectively. Semen hyaluronidase activities in group D rams also increased significantly (p<0.001) in comparison with the control group at all times except 72 and 384 hr. Serum hyaluronidase activities increased significantly (p<0.01, <0.001) at 24 and 48 hr after treatment of lincomycin-spectinomycin. Additionally, significant (p<0.05, <0.001) increases were detected in the serum hyaluronidase activities of group D at 48 and 72 hr, respectively. No significant correlation was found between serum and semen hyaluronidase activities. Furthermore, significant increases (p<0.05) were observed in the percentages of motile sperm in the rams of group C and D compared with the control groups. The values of sperm concentration and total number of sperm in group C and D rams decreased significantly (p<0.001) in comparison with control groups. No significant correlations were found between the semen hyaluronidase activities and sperm characteristics. In conclusion, these findings show that the combinations of lincomycin-spectinomycin and sulfamethoxazole-trimethoprim do not have any harmful effects on hyaluronidase activities and sperm motility. However, the use of both antibiotic combinations in breeding rams during the ramming season is not advisable due to the decrease of sperm concentration.
Keywords: acrosomal enzyme; antibiotic; motility